Preparation method of aramid / aluminum oxide composite diaphragm
Patent Information
- Application Number
- CN202610151248.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-03
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-02-03
AI Technical Summary
目前锂电池隔膜主要以聚烯烃材料,但这种材料的熔点较低,当电池因内部或外部因素温度升高时,聚烯烃多孔膜可能会收缩或熔融,导致正负极直接接触,引发短路,进而可能引起电池燃烧或爆炸等安全事故
采用本发明的制备方法制备的芳纶/氧化铝复合隔膜厚度均匀,孔隙率高,电解液浸润时间短,剥离强度高,综合性能优异,将其应用于锂离子电池,可以提高锂离子电池的容量和循环性能。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery separator technology, and in particular to a method for preparing an aramid / alumina composite separator. Background Technology
[0002] Lithium-ion batteries, with their significant advantages such as wide operating temperature range, high output voltage, no memory effect, and long cycle life, have become indispensable energy storage and conversion devices in everyday electronic devices. The separator is one of the key components of a lithium battery, determining the battery's interface structure, internal resistance, and other characteristics, directly affecting its capacity, cycle life, and safety performance. The main function of the separator is to separate the positive and negative electrodes, preventing short circuits caused by contact between them. It also allows electrolyte ions to pass through. The performance of the separator determines the battery's interface structure, internal resistance, capacity, cycle performance, and especially has a significant impact on battery safety. Currently, lithium battery separators are mainly made of polyolefin materials. However, this material has a low melting point. When the battery temperature rises due to internal or external factors, the porous polyolefin membrane may shrink or melt, causing direct contact between the positive and negative electrodes, leading to a short circuit, and potentially causing safety accidents such as battery combustion or explosion.
[0003] To address this issue, inorganic particles are typically coated onto the surface of a membrane substrate using an adhesive to create a composite membrane. For example, ceramic particles can be coated onto the membrane substrate to form a ceramic / polymer composite membrane, utilizing the heat resistance of the ceramic particles to reduce thermal shrinkage. However, the overall performance of the membrane depends not only on the materials used but also on the uniformity of the inorganic particle dispersion and the membrane molding process. Therefore, improving the uniformity of inorganic particle dispersion and refining the membrane molding process to enhance its overall performance has become a critical technical challenge that needs to be addressed by those skilled in the art. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing an aramid / alumina composite membrane to solve the problems existing in the prior art.
[0005] To achieve the above objectives, the present invention provides the following solution: One of the technical solutions of the present invention: a method for preparing an aramid / alumina composite separator, comprising the following steps: Alumina particles, aramid fibers, polymer binders, and dispersants are added to an organic solvent and dispersed evenly to obtain a suspension. The suspension is coated onto the base membrane, dried, and then subjected to micro-pressure treatment to obtain the aramid / alumina composite membrane.
[0006] Preferably, the mass ratio of the alumina particles, aramid fiber, polymer binder and dispersant is (80~90):(15~25):(8~10):(1.2~1.5).
[0007] Preferably, the alumina particles have a particle size of 2~10μm; The polymer binder includes one or more of polyacrylic acid, polyvinylidene fluoride, and polyethyleneimine; The dispersant includes one or more of sodium dodecylbenzenesulfonate, dodecyltrimethylammonium chloride, glycerol, and sorbitol.
[0008] Preferably, the dispersion method includes: stirring followed by high-speed microjet shearing; Preferably, the pressure of the microjet high-speed shear is 1800~2200 bar, the number of cycles is 3~5, the solid content is 10~15%, the volume of the microchannel is 75~100 μm, the feed rate is 500~600 mL / h, and the feed temperature is ≤40℃.
[0009] Preferably, the coating speed is 4~6 m / min.
[0010] Preferably, the drying process includes pre-curing at 75-85°C and then drying at 105-115°C to constant weight.
[0011] Preferably, the temperature of the micro-pressure treatment is 55~65℃ and the pressure is 0.8~1.2MPa.
[0012] Preferably, the method for preparing the aramid / alumina composite membrane further includes a step of subjecting the aramid fibers to low-temperature plasma treatment before preparing the suspension; The parameters for the low-temperature plasma treatment include: a power of 200-300W, an atmosphere of a mixture of hydrogen, fluorine and helium, a gas pressure of 500-1000Pa, a temperature of 80-120℃, and a time of 10-15min.
[0013] The second technical solution of the present invention: an aramid / alumina composite membrane prepared by the above preparation method.
[0014] The third technical solution of the present invention: an application of the above-mentioned aramid / alumina composite separator as a lithium-ion battery separator.
[0015] The present invention discloses the following technical effects: The aramid / alumina composite separator prepared by the method of the present invention has uniform thickness, high porosity, short electrolyte wetting time, high peel strength, and excellent overall performance. When applied to lithium-ion batteries, it can improve the capacity and cycle performance of lithium-ion batteries. Detailed Implementation
[0016] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0017] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0018] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0019] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0020] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0021] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.
[0022] This invention discloses a method for preparing an aramid / alumina composite separator, comprising the following steps: Alumina particles, aramid fibers, polymer binders, and dispersants are added to an organic solvent and dispersed evenly to obtain a suspension. A suspension is coated onto a base membrane, dried, and then subjected to micro-pressure treatment to obtain an aramid / alumina composite membrane.
[0023] In some optional embodiments, the mass ratio of alumina particles, aramid fibers, polymer binder and dispersant is (80~90):(15~25):(8~10):(1.2~1.5).
[0024] In some optional embodiments, the alumina particles have a particle size of 2~10 μm; In some alternative embodiments, the polymer binder includes one or more of polyacrylic acid, polyvinylidene fluoride, and polyethyleneimine; In some optional embodiments, the dispersant includes one or more of sodium dodecylbenzenesulfonate, dodecyltrimethylammonium chloride, glycerol, and sorbitol.
[0025] In some optional embodiments, the dispersion method includes: mechanical stirring followed by high-speed microjet shearing; by adopting a composite dispersion process of mechanical stirring and high-speed microjet shearing, the alumina particles can be distributed in a highly uniform state in the suspension containing aramid fibers, which is conducive to effectively embedding and fixing the alumina particles in the three-dimensional network composed of aramid fibers, thereby forming a dense composite coating without macroscopic agglomeration.
[0026] The pressure of the microjet high-speed shearing is 1800~2200 bar, the number of cycles is 3~5, the solid content is 10~15%, the volume of the microchannel is 75~100μm, the feed rate is 500~600mL / h, and the feed temperature is ≤40℃.
[0027] In some optional embodiments, the coating speed is 4 to 6 m / min; at this coating speed, the leveling properties of the coating are better and the resulting coating thickness is more uniform. If the coating speed is too fast, it will induce capillary effect, resulting in longitudinal stripes on the coating.
[0028] In some optional embodiments, drying includes pre-curing at 75-85°C and then drying at 105-115°C to constant weight. Using a stepped heating method effectively avoids surface "skinning" and the formation of internal bubbles, increases the porosity of the coating, and shortens the electrolyte wetting time.
[0029] In some optional embodiments, the temperature of the micro-pressure treatment is 55~65°C and the pressure is 0.8~1.2MPa; the micro-pressure treatment can improve the peel strength of the coating without significantly negatively affecting the porosity.
[0030] In some optional embodiments, the method for preparing the aramid / alumina composite membrane further includes a step of subjecting the aramid fibers to low-temperature plasma treatment before preparing the suspension; The parameters for low-temperature plasma treatment include: power of 200~300W, atmosphere of mixed atmosphere of hydrogen, fluorine and helium, gas pressure of 500~1000Pa, temperature of 80~120℃, and time of 10~15min.
[0031] Aramid fiber is a high-performance fiber that can withstand temperatures above 400℃, possesses excellent fire resistance and flame retardancy, and exhibits superior mechanical properties. However, untreated aramid fibers have a highly inert surface and low surface energy, resulting in less than ideal wetting performance with electrolytes. When aramid fibers undergo low-temperature plasma treatment, the high-energy particles in the plasma not only etch micro-grooves into the fiber surface, increasing surface roughness, but also break the chemical bonds on the fiber surface, introducing polar groups such as hydroxyl, carboxyl, and amino groups. This enhances the wetting ability of aramid fibers with electrolytes, increases electrolyte absorption, and creates efficient channels for lithium-ion migration. Furthermore, the treated aramid fibers can better integrate with the base membrane, retaining their high-temperature stability while further improving the spatial stability and flatness of the separator through a strong bond with the base membrane. Applying this to lithium-ion batteries solves problems such as poor electrolyte absorption and susceptibility to breakage found in ordinary separators, significantly improving the battery's electrochemical performance, safety performance, and cycle life, thus meeting the long-life requirements of high-end batteries.
[0032] This invention also discloses an aramid / alumina composite membrane prepared by the above preparation method.
[0033] This invention also discloses an application of the above-mentioned aramid / alumina composite separator as a lithium-ion battery separator.
[0034] Example 1 A method for preparing an aramid / alumina composite membrane: (1) Alumina particles (particle size 3.5 μm, specific surface area 1.1105 m²) 2 Aramid fiber, polymer binder (polyacrylic acid, average molecular weight of 400 g / mol), and dispersant (sodium dodecylbenzenesulfonate) were added to N,N-dimethylformamide (DMF) in a mass ratio of 85:20:8:1.3. The mixture was first stirred at 800 r / min for 30 min, and then subjected to high-speed shear dispersion by microjets to obtain a suspension with an alumina particle content of 12 wt.%. The parameters for the microjet high-speed shearing are: pressure of 2000 bar, number of cycles of 5, solid content of 12%, microchannel volume of 75 μm, feed rate of 600 mL / h, and feed temperature of ≤40℃.
[0035] (2) The diaphragm slurry was coated (coating speed was 5 m / min) onto both sides of a polyethylene (PE) membrane with a thickness of 13 μm. After drying (pre-curing at 80℃ and then drying at 110℃ to constant weight), micro-pressure treatment was performed (temperature was 60℃ and pressure was 1.0 MPa) to obtain an aramid / ceramic composite diaphragm with a thickness of about 16 μm.
[0036] Example 2 A method for preparing an aramid / alumina composite membrane: (1) Alumina particles (particle size 2μm, specific surface area 1.3306m²) 2 Alumina, aramid fiber, polymer binder (polyvinylidene fluoride, average molecular weight 70000 g / mol), and dispersant (dodecyltrimethylammonium chloride) were added to N,N-dimethylformamide (DMF) in a mass ratio of 80:25:9:1.5. The mixture was first stirred at 800 r / min for 30 min, and then subjected to high-speed shear dispersion by microjets to obtain a suspension with an alumina particle content of 15 wt.%. The parameters for high-speed microjet shearing are: pressure of 2200 bar, number of cycles of 3, solid content of 15 wt.%, microchannel volume of 100 μm, feed rate of 500 mL / h, and feed temperature of ≤40℃.
[0037] (2) The diaphragm slurry was coated (coating speed was 4 m / min) onto both sides of a polyethylene (PE) membrane with a thickness of 13 μm. After drying (pre-curing at 75℃ and then drying at 115℃ to constant weight), micro-pressure treatment was performed (temperature was 55℃ and pressure was 1.2 MPa) to obtain an aramid / ceramic composite diaphragm with a thickness of about 15.8 μm.
[0038] Example 3 A method for preparing an aramid / alumina composite membrane: (1) Alumina particles (particle size 10 μm, specific surface area 0.6146 m²) 2 Alumina, aramid fiber, polymer binder (polyethyleneimine, average molecular weight 3000 g / mol), and dispersant (sorbitol) were added to N,N-dimethylformamide (DMF) in a mass ratio of 90:15:8:1.2. The mixture was first stirred at 800 r / min for 30 min, and then subjected to high-speed shear dispersion by microjets to obtain a suspension with an alumina particle content of 10 wt.%. The parameters for high-speed microjet shearing are: pressure of 1800 bar, number of cycles of 5, solid content of 10 wt.%, microchannel volume of 75 μm, feed rate of 550 mL / h, and feed temperature of ≤40℃.
[0039] (2) The diaphragm slurry was coated (coating speed was 6 m / min) onto both sides of a polyethylene (PE) membrane with a thickness of 13 μm. After drying (pre-curing at 85℃ and then drying at 105℃ to constant weight), micro-pressure treatment was performed (temperature was 65℃ and pressure was 0.8 MPa) to obtain an aramid / ceramic composite diaphragm with a thickness of about 16.1 μm.
[0040] Comparative Example 1 Same as Example 1, except that the step of high-speed shear dispersion using microjets is omitted, and the dispersibility is improved by increasing the stirring speed. Specifically, step (1) is as follows: alumina particles (particle size of 3.5 μm, specific surface area of 1.1105 m²) are dispersed in the alumina solution. 2 Alumina particles (6g), aramid fiber, polymer binder (polyacrylic acid, average molecular weight 400 g / mol), and dispersant (sodium dodecylbenzenesulfonate) were added to N,N-dimethylformamide (DMF) in a mass ratio of 85:20:8:1.3. The mixture was stirred at 1200 r / min for 30 min to obtain a suspension with an alumina particle content of 12 wt.%.
[0041] Comparative Example 2 Same as Example 1, except that the coating speed in step (2) is 10 m / min.
[0042] Comparative Example 3 Same as Example 1, except that the drying conditions in step (2) are: drying at 110°C to constant weight.
[0043] Comparative Example 4 Same as Example 1, except that micro-pressure treatment was not performed. Specifically, the membrane slurry was coated (coating speed was 5m / min) onto both sides of a 13μm thick polyethylene (PE) membrane and dried (first pre-cured at 80℃, then dried at 110℃ to constant weight) to obtain an aramid / ceramic composite membrane with a thickness of about 16μm.
[0044] Example 4 A method for preparing an aramid / alumina composite membrane: (1) The aramid fiber was subjected to low-temperature plasma treatment. The parameters of the low-temperature plasma treatment were as follows: power of 250W, atmosphere of mixed atmosphere of hydrogen, fluorine and helium with a volume ratio of 96:1:3, gas pressure of 700Pa, temperature of 105℃, and time of 15min; after the treatment, pretreated aramid fiber was obtained.
[0045] (2) Alumina particles (particle size 3.5 μm, specific surface area 1.1105 m²) 2 / g), pretreated aramid fiber, polymer binder (polyacrylic acid, average molecular weight of 400 g / mol) and dispersant (sodium dodecylbenzenesulfonate) were added to N,N-dimethylformamide (DMF) in a mass ratio of 85:20:8:1.3. The mixture was first stirred at 800 r / min for 30 min, and then subjected to high-speed shear dispersion by microjets to obtain a suspension with an alumina particle content of 12 wt.%. The parameters for high-speed microjet shearing are: pressure of 2000 bar, number of cycles of 5, solid content of 12 wt.%, microchannel volume of 75 μm, feed rate of 600 mL / h, and feed temperature of ≤40℃.
[0046] (3) The diaphragm slurry was coated (coating speed was 5 m / min) onto both sides of a polyethylene (PE) membrane with a thickness of 13 μm. After drying (pre-curing at 80℃ and then drying at 110℃ to constant weight), micro-pressure treatment was performed (temperature was 60℃ and pressure was 1.0 MPa) to obtain an aramid / ceramic composite diaphragm with a thickness of 16 μm.
[0047] Example 5 A method for preparing an aramid / alumina composite membrane: (1) The aramid fiber was subjected to low-temperature plasma treatment. The parameters of the low-temperature plasma treatment were as follows: power of 300W, atmosphere of mixed atmosphere of hydrogen, fluorine and helium with a volume ratio of 96:1:3, gas pressure of 800Pa, temperature of 120℃, and time of 10min; after the treatment, pretreated aramid fiber was obtained.
[0048] (2) Alumina particles (particle size 3.5 μm, specific surface area 1.1105 m²) 2 / g), pretreated aramid fiber, polymer binder (polyacrylic acid, average molecular weight of 400 g / mol) and dispersant (sodium dodecylbenzenesulfonate) were added to N,N-dimethylformamide (DMF) in a mass ratio of 85:20:8:1.3. The mixture was first stirred at 800 r / min for 30 min, and then subjected to high-speed shear dispersion by microjets to obtain a suspension with an alumina particle content of 12 wt.%. The parameters for high-speed microjet shearing are: pressure of 2000 bar, number of cycles of 5, solid content of 12 wt.%, microchannel volume of 75 μm, feed rate of 600 mL / h, and feed temperature of ≤40℃.
[0049] (3) The diaphragm slurry was coated (coating speed was 5 m / min) onto both sides of a polyethylene (PE) membrane with a thickness of 13 μm. After drying (pre-curing at 80℃ and then drying at 110℃ to constant weight), micro-pressure treatment was performed (temperature was 60℃ and pressure was 1.0 MPa) to obtain an aramid / ceramic composite diaphragm with a thickness of 16 μm.
[0050] Example 6 A method for preparing an aramid / alumina composite membrane: (1) The aramid fiber was subjected to low-temperature plasma treatment. The parameters of the low-temperature plasma treatment were as follows: power of 200W, atmosphere of mixed atmosphere of hydrogen, fluorine and helium with a volume ratio of 96:1:3, gas pressure of 1000Pa, temperature of 80℃, and time of 12min; after the treatment, pretreated aramid fiber was obtained.
[0051] (2) Alumina particles (particle size 3.5 μm, specific surface area 1.1105 m²) 2 / g), pretreated aramid fiber, polymer binder (polyacrylic acid, average molecular weight of 400 g / mol) and dispersant (sodium dodecylbenzenesulfonate) were added to N,N-dimethylformamide (DMF) in a mass ratio of 85:20:8:1.3. The mixture was first stirred at 800 r / min for 30 min, and then subjected to high-speed shear dispersion by microjets to obtain a suspension with an alumina particle content of 12 wt.%. The parameters for high-speed microjet shearing are: pressure of 2000 bar, number of cycles of 5, solid content of 12 wt.%, microchannel volume of 75 μm, feed rate of 600 mL / h, and feed temperature of ≤40℃.
[0052] (3) The diaphragm slurry was coated (coating speed was 5 m / min) onto both sides of a polyethylene (PE) membrane with a thickness of 13 μm. After drying (pre-curing at 80℃ and then drying at 110℃ to constant weight), micro-pressure treatment was performed (temperature was 60℃ and pressure was 1.0 MPa) to obtain an aramid / ceramic composite diaphragm with a thickness of 16 μm.
[0053] Example of effect 1 The coating thickness uniformity (CV value), porosity, electrolyte wetting time, and peel strength between the coating and the base film of the composite membranes prepared in the examples and comparative examples were measured. The results are shown in Table 1.
[0054] Table 1. Performance of the diaphragm Application Example 1 A lithium-ion battery comprises a positive electrode, a negative electrode, a separator, and an electrolyte. The preparation steps of the lithium-ion battery are as follows: Lithium iron phosphate (LFP): Super P: PVDF were dispersed in DMF at a mass ratio of 8:1:1, with the solid content controlled at 60% to obtain a positive electrode slurry. The positive electrode slurry was coated onto aluminum foil using a 100 μm thick scraper and dried for later use. The electrolyte composition was: 1 mol / L LiPF6 as the electrolyte and a mixture of EC:DMC (volume ratio) = 1:1 as the solvent. The separator was a composite separator prepared in the examples or comparative examples. A 100 μm thick lithium sheet was used as the counter electrode, and coin cells of model 2032 were assembled in an inert gas glove box with water and oxygen content both below 0.1 ppm. The charge capacity, discharge capacity, and capacity retention rate after 300 cycles at 0.5C were measured, and the results are shown in Table 2.
[0055] Table 2 Performance of Lithium-ion Batteries The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for preparing an aramid / alumina composite separator, characterized in that, Includes the following steps: Alumina particles, aramid fibers, polymer binders, and dispersants are added to an organic solvent and dispersed evenly to obtain a suspension. The suspension is coated onto a base membrane, dried, and then subjected to micro-pressure treatment to obtain the aramid / alumina composite membrane. The mass ratio of the alumina particles, aramid fibers, polymer binder, and dispersant is (80~90):(15~25):(8~10):(1.2~1.5). The dispersion method includes: stirring followed by high-speed microjet shearing; The pressure of the high-speed shearing of the microjet is 1800~2200 bar, the number of cycles is 3~5, the solid content is 10~15%, the volume of the microchannel is 75~100μm, the feed rate is 500~600mL / h, and the feed temperature is ≤40℃. The coating speed is 4~6 m / min; The drying process includes pre-curing at 75-85°C and then drying at 105-115°C to constant weight. The micro-pressure treatment is performed at a temperature of 55~65℃ and a pressure of 0.8~1.2MPa. The preparation method further includes a step of subjecting the aramid fibers to low-temperature plasma treatment before preparing the suspension; The parameters for the low-temperature plasma treatment include: a power of 200-300W, an atmosphere of a mixture of hydrogen, fluorine and helium, a gas pressure of 500-1000Pa, a temperature of 80-120℃, and a time of 10-15min.
2. The preparation method according to claim 1, characterized in that, The alumina particles have a particle size of 2~10μm; And / or, the polymer binder includes one or more of polyacrylic acid, polyvinylidene fluoride, and polyethyleneimine; And / or, the dispersant comprises one or more of sodium dodecylbenzenesulfonate, dodecyltrimethylammonium chloride, glycerol, and sorbitol.
3. An aramid / alumina composite membrane prepared by the preparation method according to any one of claims 1 to 2.
4. The application of the aramid / alumina composite separator as described in claim 3 as a lithium-ion battery separator.
Citation Information
Patent Citations
Modified aramid fiber reinforced PA66 material and preparation method thereof
CN103709742A
Lithium-ion battery separator subjected to composite coating treatment and preparation method thereof
CN106252565A